Do I need contraceptives during breastfeeding? - Jamani, Nurjasmine Aida (Ministry Of Health Malaysia, 2019)
“Oh no, it’s positive! How did this happen? Am I not still nursing my baby?” Aina thought to herself while holding the pregnancy test kit. She is worried as her first baby is only 4 months old.